2010
DOI: 10.1002/chem.200902543
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Asymmetric Autocatalytic Soai Reaction Studied by Density Functional Theory

Abstract: The mechanism of the Soai reaction has been thoroughly investigated at the M05-2X/6-31G(d) level of theory, by considering ten energetically distinct paths. The study indicates the fully enantioselective catalytic cycle of the homochiral dimers to be the dominant mechanism. Two other catalytic cycles are shown to both be important for correct understanding of the Soai reaction. These are the catalytic cycle of the heterochiral dimer and the non-enantioselective catalytic cycle of the homochiral dimers. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 69 publications
7
32
0
Order By: Relevance
“…N is not included in our analysis, even if a very recent study has shown that chirality caused (only) by N-isotopes can control the enantiomeric outcome of the Soai reaction [43]. Some fragments of hypothetic intermediates [44][45][46] of the Soai autocatalysis show chiral arrangement of the Zn atoms. One of these fragments, the structure of which has been essentially supported by X-ray crystallography [47], will also be included in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…N is not included in our analysis, even if a very recent study has shown that chirality caused (only) by N-isotopes can control the enantiomeric outcome of the Soai reaction [43]. Some fragments of hypothetic intermediates [44][45][46] of the Soai autocatalysis show chiral arrangement of the Zn atoms. One of these fragments, the structure of which has been essentially supported by X-ray crystallography [47], will also be included in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Reasonable theoretical efforts at the elucidation of the structure of the possible intermediates have been published on the basis of "first principles" and other calculations [44][45][46]49], as well as kinetic/calorimetric/spectroscopic measurements [51,52] (only to mention the most cited ones). Very recently, even realistically designed and prepared model compounds could be crystallized and studied by X-ray crystallography [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We supposed, the fact of exclusion of simple stochastic formalisms for the description of the absolute AAS variant of the Soai reaction might indicate a more complicated mechanism, which might be described by a more complex stochastic law. Interestingly, while we were working on the statistical approach from this point of view, Ercolani and Schiaffino [81][82][83][84][85], in a couple of excellent papers arrived qualitatively at the same conclusion, on a very different basis, by theoretical calculations, in an attempt at identifying possible intermediates of the Soai autocatalysis.…”
Section: Stochastic Approachmentioning
confidence: 99%